Pengembangan Media Pembelajaran Berbasis Game Mobile Galatya (Galileo Jelajah Tata Surya) Untuk Meningkatkan Motivasi Dan Hasil Belajar Peserta Didik Kelas Vi Sd - Grace Anggraeni Dewi; Adi Winanto (Jurnal Pendidikan Indonesia, 2025)
This research aims to develop a mobile game-based learning media with the title GALATYA (Galileo Jelajah Solar System) to improve the motivation and learning outcomes of grade VI elementary school students as the main topic in the research. The development method used is Research and Development (R&D) with three main stages including preliminary study, product development, and product testing. Data collection was carried out by three techniques, namely school observation, learning motivation questionnaires by students and teachers, and initial tests before media use and final tests after media use. The validation results by the material expert showed a score of 97% so it was included in the very feasible category, while the validation results of learning media experts obtained a score of 95% so that it was included in the very feasible category. The effectiveness of the product was tested using the Independent sample T-test, which showed a significant difference between the experimental class and the control class. Based on the results of the research, Galatya's learning media was proven to be valid based on the results of validation from material experts, media experts, and educators. In addition, Galatya is effective in improving student learning outcomes based on the independent sample t-test which shows significant differences between the experimental clas and the control class.